ReaxFF‐based molecular dynamics simulation of the interactions between OH radicals in plasma and succinate dehydrogenase in cancer cell mitochondria. Issue 12 (1st August 2022) - Wang, Huichao; Zhao, Tong; Wang, Xiaolong; Wang, Daohan; Zhang, Yuantao
Abstract: In the plasma‐induced apoptosis of cancer cells, reactive oxygen species (ROS) cause mitochondrial enzyme dysfunction and inhibit the respiration of cancer cells. In this article, we explored the microscopic reaction mechanism between succinate dehydrogenase (SDH) and the OH radicals in plasma. The results showed that the hydrogen abstraction reaction was the most basic reaction mode. The S–H bond had the highest reaction activity, and the cysteine had the highest reaction participation rate in the simulation. Increasing OH radical concentration, the damage degree of SDH increased, while the utilization rate of OH decreased. This study facilitates a new perspective of the apoptosis mechanism of cancer cells in plasma therapy and provides a reference for the clinical plasma treatment of cancer. Abstract : The OH radicals in cold atmospheric plasma cause irreversible damage to the configuration of succinate dehydrogenase. Hydrogen abstraction reaction is the basic way of OH oxidation damage to succinate dehydrogenase (SDH). Cysteine, lysine, and tyrosine were the top three amino acids involved in the reaction. The utilization rate of the OH radicals decreased increasing OH concentration, while the damaging effect was weakened.